Identification of a 6‐lncRNA prognostic signature based on microarray re‐annotation in gastric cancer. (19th November 2019) - Ma, Bin; Li, Yongmin; Ren, Yupeng
Abstract: Gastric cancer (GC) remains an important malignancy worldwide with poor prognosis. Long noncoding RNAs (lncRNAs) can markedly affect cancer progression. Moreover, lncRNAs have been proposed as diagnostic or prognostic biomarkers of GC. Therefore, the current study aimed to explore lncRNA‐based prognostic biomarkers for GC. LncRNA expression profiles from the Gene Expression Omnibus (GEO) database were first downloaded. After re‐annotation of lncRNAs, a univariate Cox analysis identified 177 prognostic lncRNA probes in the training set GSE62254 (n = 225). Multivariate Cox analysis of each lncRNA with clinical characteristics as covariates identified a total of 46 prognostic lncRNA probes. Robust likelihood‐based survival and least absolute shrinkage and selection operator (LASSO) models were used to establish a 6‐lncRNA signature with prognostic value. Receiver operating characteristic (ROC) curve analyses were employed to compare survival prediction in terms of specificity and sensitivity. Patients with high‐risk scores exhibited a significantly worse overall survival (OS) than patients with low‐risk scores (log‐rank test P ‐value <.0001), and the area under the ROC curve (AUC) for 5‐year survival was 0.77. A nomogram and forest plot were constructed to compare the clinical characteristics and risk scores by a multivariable Cox regression analysis, which suggested that the 6‐lncRNA signature can independently make the prognosis evaluation of patients. Single‐sample GSEA (ssGSEA) was used to determine the relationships between the 6‐lncRNA signature and biological functions. The internal validation set GSE62254 (n = 75) and the external validation set GSE57303 (n = 70) were successfully used to validate the robustness of our 6‐lncRNA signature. In conclusion, based on the above results, the 6‐lncRNA signature can effectively make the prognosis evaluation of GC patients. Abstract : Identification of a 6‐lncRNA prognostic signature based on microarray re‐annotation in gastric cancer